Golden Orbweavers Ignore Biological Rules: Phylogenomic and Comparative Analyses Unravel a Complex Evolution of Sexual Size Dimorphism - Kuntner, Matjaž; Hamilton, Chris A; Cheng, Ren-Chung; Gregorič, Matjaž; Lupše, Nik; Lokovšek, Tjaša; Lemmon, Emily Moriarty; Lemmon, Alan R; Agnarsson, Ingi; Coddington, Jonathan A; Bond, Jason E (Systematic biology, 2019)
Instances of sexual size dimorphism (SSD) provide the context for rigorous tests of biological rules of size evolution, such as Cope's rule (phyletic size increase), Rensch's rule (allometric patterns of male and female size), as well as male and female body size optima. In certain spider groups, such as the golden orbweavers (Nephilidae), extreme female-biased SSD (eSSD, female:male body length $\ge$2) is the norm. Nephilid genera construct webs of exaggerated proportions, which can be aerial, arboricolous, or intermediate (hybrid). First, we established the backbone phylogeny of Nephilidae using 367 anchored hybrid enrichment markers, then combined these data with classical markers for a reference species-level phylogeny. Second, we used the phylogeny to test Cope and Rensch's rules, sex specific size optima, and the coevolution of web size, type, and features with female and male body size and their ratio, SSD. Male, but not female, size increases significantly over time, and refutes Cope's rule. Allometric analyses reject the converse, Rensch's rule. Male and female body sizes are uncorrelated. Female size evolution is random, but males evolve toward an optimum size (3.2-4.9 mm). Overall, female body size correlates positively with absolute web size. However, intermediate sized females build the largest webs (of the hybrid type), giant female Nephila and Trichonephila build smaller webs (of the aerial type), and the smallest females build the smallest webs (of the arboricolous type). We propose taxonomic changes based on the criteria of clade age, monophyly and exclusivity, classification information content, and diagnosability. Spider families, as currently defined, tend to be between 37 million years old and 98 million years old, and Nephilidae is estimated at 133 Ma (97-146), thus deserving family status. We, therefore, resurrect the family Nephilidae Simon 1894 that contains Clitaetra Simon 1889, the Cretaceous GeratonephilaPoinar and Buckley (2012), Herennia Thorell 1877, IndoetraKuntner 2006, new rank, Nephila Leach 1815, Nephilengys L. Koch 1872, Nephilingis Kuntner 2013, Palaeonephila Wunderlich 2004 from Tertiary Baltic amber, and TrichonephilaDahl 1911, new rank. We propose the new clade Orbipurae to contain Araneidae Clerck 1757, Phonognathidae Simon 1894, new rank, and Nephilidae. Nephilid female gigantism is a phylogenetically ancient phenotype (over 100 Ma), as is eSSD, though their magnitudes vary by lineage.
Keywords: Phylogeny; velikost těla; Sex Characteristics; Male; Animals; Female; mužské pohlaví; ženské pohlaví; pavouci; pohlavní dimorfismus; Body Size; zvířata; fylogeneze; Spiders